Circulating CD8+ mucosal‐associated invariant T cells correlate with improved treatment responses and overall survival in anti‐PD‐1‐treated melanoma patients. Issue 1 (10th January 2022) - Vorwald, Victoria M; Davis, Dana M; Van Gulick, Robert J; Torphy, Robert J; Borgers, Jessica SW; Klarquist, Jared; Couts, Kasey L; Amato, Carol M; Cogswell, Dasha T; Fujita, Mayumi; Castleman, Moriah J; Davis, Timothy; et al.
Abstract: Objectives: While much of the research concerning factors associated with responses to immune checkpoint inhibitors (ICIs) has focussed on the contributions of conventional peptide‐specific T cells, the role of unconventional T cells, such as mucosal‐associated invariant T (MAIT) cells, in human melanoma remains largely unknown. MAIT cells are an abundant population of innate‐like T cells expressing a semi‐invariant T‐cell receptor restricted to the MHC class I‐like molecule, MR1, presenting vitamin B metabolites derived from bacteria. We sought to characterise MAIT cells in melanoma patients and determined their association with treatment responses and clinical outcomes. Methods: In this prospective clinical study, we analysed the frequency and functional profile of circulating and tumor‐infiltrating MAIT cells in human melanoma patients. Using flow cytometry, we compared these across metastatic sites and between ICI responders vs. non‐responders as well as healthy donors. Results: We identified tumor‐infiltrating MAIT cells in melanomas across metastatic sites and found that the number of circulating MAIT cells is reduced in melanoma patients compared to healthy donors. However, circulating MAIT cell frequencies are restored by ICI treatment in responding patients, correlating with treatment responses, in which patients with high frequencies of MAIT cells exhibited significantly improved overall survival. Conclusion: Our results suggest that MAIT cells may be a potential predictive marker of responses to immunotherapies and provide rationale for testing MAIT cell‐directed therapies in combination with current and next‐generation ICIs. Abstract : While the number of circulating MAIT cells is reduced in melanoma patients, circulating MAIT cell frequency is restored by immune checkpoint inhibitor treatment in responding patients, correlating with treatment responses, in which patients with high frequencies of MAIT cells exhibited significantly improved overall survival.